Reverse ray tracing of the mesospheric gravity waves observed over Indian low-latitude region - Chauhan, Nilesh; Gurubaran, Subramanian; Lakshmi Narayanan, Viswanathan (My University, 2022)
Gravity wave observations from the all-sky airglow imaging of OH emission from Tirunelveli (8.7°N, 77.8°E) during the year 2007. The characteristics of the observed wave events are presented in Narayanan et.al, 2013. A total of 261 wave events were observed from January 2007 to November 2007. The whole dataset from (Narayanan et.al, 2013) is used here to study the extent of lower atmospheric forcing. The background wind information was obtained from co-located MF Radar from which the intrinsic wave parameters are estimated. The horizontal wavelengths ranged over 10-50 km, the periods ranged from 3 to 40 min and the phase speeds were in the range 20-150 m/s. The present work is an effort to study the propagation of those gravity waves through the middle atmosphere and assess their source regions using reverse ray tracing technique. The HWM-14 model for wind and NRLMSIS-00 model for temperature were used in the present analysis. The analysis was carried out for scenarios: i) HWM winds and ii) Zero wind condition. The initial results showed that majority of the ray paths stopped in the mesosphere at levels where the imposed condition of m 2 < 0. Further results and a discussion on the nature of identified waves and their corresponding sources are presented in this study.
Keywords: Reverse ray tracing; Mesosphere; Gravity waves; Indian low latitudes